2021
DOI: 10.3390/vaccines10010006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Measles Vaccine Hesitancy among Sudanese Parents in Khartoum State, Sudan: A Cross-Sectional Study

Abstract: Determinants of vaccine hesitancy are not yet well understood. This study aims to assess measles vaccine hesitancy and characterize its determinants among Sudanese parents in Omdurman in Khartoum State. A community-based cross-sectional quantitative study was conducted in Khartoum State in February 2019. The Parent Attitudes about Childhood Vaccination (PACV) was used to measure measles vaccine hesitancy. Questions about the sociodemographic characteristics of the family, the perception of the parents about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
12
2
Order By: Relevance
“…Given the complexity of the relationship between supply-side and demand-side factors and measles vaccine hesitancy as suggested by previous studies in Sudan [29,43], different approaches should be adopted to address vaccine hesitancy to increase the uptake of measles vaccine in Sudan. For the demand side, previous findings in Sudan have shown that parental exposure to anti-vaccine information is predicting measles vaccine hesitancy among them [43]. We suggest that communication strategies be theory and evidence based to address the behavioral determinants of vaccine hesitancy, such as knowledge of, beliefs about, and attitude toward measles and measles vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the complexity of the relationship between supply-side and demand-side factors and measles vaccine hesitancy as suggested by previous studies in Sudan [29,43], different approaches should be adopted to address vaccine hesitancy to increase the uptake of measles vaccine in Sudan. For the demand side, previous findings in Sudan have shown that parental exposure to anti-vaccine information is predicting measles vaccine hesitancy among them [43]. We suggest that communication strategies be theory and evidence based to address the behavioral determinants of vaccine hesitancy, such as knowledge of, beliefs about, and attitude toward measles and measles vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons behind the low uptake of the measles vaccine are not fully understood. Data from Sudan suggest the existence of measles vaccine hesitancy in Sudan, with several social and behavioral drivers behind this hesitancy [26,29,43]. In this study, we aimed to evaluate whether measles vaccine uptake is predicted by measles vaccine hesitancy.…”
Section: Introductionmentioning
confidence: 99%
“…This study is part of a large research project about measles vaccine hesitancy in Sudan [ 21 , 22 ]. The sample size was calculated for the whole research using a power analysis for the association between measles vaccine hesitancy and the measles vaccination status (outcome), which showed that at least 386 participants were needed to yield an 80% power to detect an odds ratio of 1.7 at alpha level (5%).…”
Section: Methodsmentioning
confidence: 99%
“…The national measles vaccination coverage is the lowest among all child vaccinations (i.e., for the first and the second dose of measles-containing vaccine, 88% and 72%, respectively) and is lower than the required level of 95% coverage for measles elimination [ 20 ]. Previous studies in Sudan showed the existence of measles vaccine hesitancy is attributed to different drivers including vaccination access-related issues, such as the parental perception that measles vaccination services are unavailable and inaccessible [ 7 , 21 ]. Additionally, a study found that the uptake of the measles vaccine among children is predicted by their parental hesitancy toward the measles vaccine [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The national measles vaccination coverage is the lowest among all child vaccinations (i.e., the first and the second dose of measles-containing vaccine, 88%, and 72%, respectively). [20] Previous studies in Sudan showed the existence of measles vaccine hesitancy is attributed to different drivers including vaccination access-related issues such as the parental perception that measles vaccination services are unavailable and inaccessible [7,21]. Additionally, a study found that the uptake of the measles vaccine among children is predicted by their parental hesitancy toward the measles vaccine [22].…”
Section: Introductionmentioning
confidence: 99%